Stress Analysis of the Contact Deformation of Gear Shaving - Cai Anjiang; Feng Xinyang; Li Lixia; Liu Lei (Jixie chuandong)
The elastic plastic deformation of the tooth contact deformation area is an important factor which influences the concave error of shaving teeth. The application of Hertz theory to establish the shaving process contact deformation area in local coordinate system,the elastic plastic stress analysis model is constructed,the contact deformation region of the elastic and plastic stress of shaving is analyzed,the calculation formula and the plastic deformation stress calculation formula of the residual stress in contact area degeneration the elastic is put forward,the elastic limit yield stress value of shaving process contact deformation region is got,and this value as a criterion,as distinguished by the deformation area of contact gear elastic deformation and plastic deformation theory of boundary value,a method for quantitative analysis by the property of deformation of elastic-plastic deformation area of contact shaving gear is provided.